Arylation of Amide and Urea C(sp3)–H Bonds with Aryl Tosylates Generated In Situ from Phenols - Gui, Yong-Yuan; Chen, Xiao-Wang; Zhou, Wen-Jun; Yu, Da-Gang (Synlett, 2017)
The arylation of amide and urea C(sp3)–H bonds with aryl tosylates generated in situ from phenols has been realized at room temperature by combining visible-light-photoredox catalysis, hydrogen-atom-transfer catalysis, and nickel catalysis. This streamlined protocol permits rapid functionalization of phenols and direct transformation of α-amino C(sp3)–H bonds. The C(sp3)–H arylation products are obtained in high yields with good functional-group tolerance at low catalyst loadings.
Keywords: phenols; arylation; amides; ureas; nickel catalysis; photocatalysis